Pudełko Srebrne do Hoſtyi bez przykrywadła. O sposobach określania przedmiotów w inwentarzach kościelnych - Żuraszek-Ryś, Iwona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
This article focuses on methods of specifying mobile objects in the ecclesiastical inventories. The research material comes from the manuscript entitled: The revision of the treasury of the Poznań cathedral (Revisio Thesauri Ecelesiae Cathedralis Poznaniensis), which is located in the Archives of the Archdiocese of Poznań under the inventory number DK pap IV/003. This document was drawn up on 6th July 1719 and certifies revision of the treasury of the cathedral in Poznań. The person who was preparing this document had to face the difficulty of describing objects located in the treasury by means of appropriate language. The choice of objects was not a coincidence. Descriptions were used for identification of relevant specimen and had to be as precise and comprehensive so that it was possible to identify a relevant object. The specifications of mobile items stored in the treasury have the analytic form of different length that mainly depends on a number of objects with the same functions. The more such objects were stored, the more elaborated description had to be attached that would include more differentiating factors. The Polish name of the object was an obligatory part of these syntactic and semantic language structures. The description also specifies: a kind of material the item was made of, its appearance, size, purpose for which it was used, a number of subsequent items of the same kind as well as the data concerning founders and owners of those objects.